2022
DOI: 10.1177/15266028221081074
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Ischemia After Thoracoabdominal Aortic Aneurysms Endovascular Repair: From the Italian Multicenter Fenestrated/Branched Endovascular Aneurysm Repair Registry

Abstract: Purpose: The aim of this study is to report an Italian multicenter experience analyzing the incidence and the risk factors associated with spinal cord ischemia (SCI) in a large cohort of thoracoabdominal aortic aneurysms (TAAAs) treated by fenestrated-branched endovascular aneurysm repair (F-/B-EVAR). Materials and Methods: All consecutive patients undergoing F-/B-EVAR in 4 Italian university centers between 2008 and 2019 were prospectively recorded and retrospectively analyzed. Spinal cord ischemia, 30 day/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…A large extent of aortic coverage is significantly associated with an increased risk of paraplegia, as shown in a recent large analysis by the US Aortic Consortium (n = 1681 patients; OR 4.79; 95% CI 4.77-4.81; p < 0.001) [3] and a multicenter Italian cohort treated for thoracoabdominal aneurysms of Crawford extents I-III (n = 351 patients; OR 20.90; 95% CI 2.69-162.57; p < 0.004) [18]. Feezor et al concluded that the risk of SCI is increased by 30% for every 2 cm of additional thoracic aortic coverage [21].…”
Section: • Length Of Aortic Coveragementioning
confidence: 85%
See 1 more Smart Citation
“…A large extent of aortic coverage is significantly associated with an increased risk of paraplegia, as shown in a recent large analysis by the US Aortic Consortium (n = 1681 patients; OR 4.79; 95% CI 4.77-4.81; p < 0.001) [3] and a multicenter Italian cohort treated for thoracoabdominal aneurysms of Crawford extents I-III (n = 351 patients; OR 20.90; 95% CI 2.69-162.57; p < 0.004) [18]. Feezor et al concluded that the risk of SCI is increased by 30% for every 2 cm of additional thoracic aortic coverage [21].…”
Section: • Length Of Aortic Coveragementioning
confidence: 85%
“…In the same retrospective review of the Vascular Quality Initiative database of 9506 patients who had undergone extensive endovascular repair, multivariate regression revealed that aortic dissection was an independent factor for postoperative SCI (OR 1.65; 95% CI 1.26-2.16; p < 0.001). However, the main parameter associated with SCI is the extent of the aneurysm and consequently the length of aortic coverage [3,18]. In addition, preoperative occlusion of one or both hypogastric or subclavian arteries contributes to reducing alternative inflow routes to the spinal collateral network.…”
Section: • Patient Anatomical Factorsmentioning
confidence: 99%
“…Factors contributing to this heightened risk in acute cases include hemodynamic instability, longer aortic coverage for effective disease exclusion, non-staged procedures, and limitations in the usage of the available adjuncts for spinal cord protection. While many risk factors are non-modifiable preoperatively, it is crucial to emphasize vigilant patient monitoring and prompt application of available tools to prevent or mitigate this life-threatening event as swiftly as possible [74][75][76][77] .…”
Section: Multidisciplinary Team-led Managementmentioning
confidence: 99%
“…Spinal cord ischemia (SCI) is one of the most dreadful complications in patients who undergo TAAA OSR, and it may affect both perioperative and long-term outcomes because of multiple and severe medical complications directly related to the neurologic damage [10][11][12][13]. Cerebrospinal fluid drainage (CSFD) is an adjunct that has been proven to be effective in SCI prevention in TAAA OSR in randomized controlled trials and metaanalyses, and its usage is also suggested by the most recent guidelines [14,15].…”
Section: Patient Preparation Surgical Technique Intra-and Postoperati...mentioning
confidence: 99%